2014
DOI: 10.1016/j.ajhg.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Genetics Professionals Toward the Return of Incidental Results from Exome and Whole-Genome Sequencing

Abstract: Professional recommendations for the return of results from exome and whole-genome sequencing (ES/WGS) have been controversial. The lack of clear guidance about whether and, if so, how to return ES/WGS incidental results limits the extent to which individuals and families might benefit from ES/WGS. The perspectives of genetics professionals, particularly those at the forefront of using ES/WGS in clinics, are largely unknown. Data on stakeholder perspectives could help clarify how to weigh expert positions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 29 publications
2
94
0
Order By: Relevance
“…In response to the ensuing academic debate and call for revision from numerous genetic professionals and providers , the ACMG guidelines were re-issued the following year and an opt-out policy was recommended for patients who did not want to discover incidental findings [10][11][12][13][14].…”
Section: Though Tumor Sequencing Platforms Vary By Technique Germ-limentioning
confidence: 99%
“…In response to the ensuing academic debate and call for revision from numerous genetic professionals and providers , the ACMG guidelines were re-issued the following year and an opt-out policy was recommended for patients who did not want to discover incidental findings [10][11][12][13][14].…”
Section: Though Tumor Sequencing Platforms Vary By Technique Germ-limentioning
confidence: 99%
“…A similar survey of genetics professionals also found that, "The vast majority (81%) thought that individual preferences should guide return [of secondary findings]. " 10 Analysis of survey items that were informed by medical ethical principles revealed four factors or underlying topics of importance to ACMG members, including (i) best practices surrounding clinical exome or genome sequencing; (ii) respect for patient preferences regarding secondary findings when performing exome or genome sequencing; (iii) the need for clinician and laboratory guidance regarding secondary findings; and (iv) the informed consent process for secondary findings. These constructs should be considered as the ACMG and other organizations address issues pertaining to analysis and reporting of secondary findings from exome or genome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings have been variously labeled as medically actionable "incidental" or "secondary" findings, and precisely how to deal with them in terms of analysis and reporting has been a matter of considerable debate. [8][9][10] For the purposes of this article, we follow the recommendation of the Presidential Commission on Bioethical Issues and use the term "secondary finding, " which is defined as a result that is not the primary target of the test but an additional result that is actively sought, as recommended by an expert body or by a consensus of practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have already investigated the expectations, views, and attitudes toward receiving (secondary) findings from sequencing among African Americans 3 and non-African Americans 4 ; among genetic, 5 pediatric, 6 primary care, 7 and nonmedical health professionals 8 ; and about sequencing in patients with Lynch syndrome 9 as well as newborns 10 and children. 11 Several studies went beyond views and addressed intentions, 12 knowledge, awareness, and understanding 13 ; whereas others focused on the practical aspects of how to integrate sequencing in health-care practice 14 ; how to deliver the service 15 ; how to prepare different health professionals such as nurses 16 and genetic counselors 17 for their role in the delivery; how to design the patient report 18 ; and how to handle informed consent in adults, 19 children, 20 and in families with genetic disease.…”
Section: © American College Of Medical Genetics and Genomicsmentioning
confidence: 99%